ZONASI TUMBUHAN UTAMA PENYUSUN MANGROVE BERDASARKAN TINGKAT SALINITAS AIR LAUT DI DESA TELING KECAMATAN TOMBARIRI - Kendy H. Kolinug; Martina A. Langi; Semuel P. Ratag; Wawan Nurmawan (COCOS, 2014)
ABSTRACTThis research was conducted to test the relation between salinity and distribution pattern of mangrove vegetation in Teling, district of Tombariri. This research aimed to describe the distribution of main zones of mangrove plant species in relation to the salinity of sea water in Teling, district of Tombariri. This research was conducted from July to August 2014 at the mangrove forest at Teling, the district of Tombariri, North Sulawesi. This research used the combination of plot and line method. There is mangrove zonation in Teling District of Tombariri which consists of (from the sea to the mainland) Sonneratia zone (zone 1), Rhizophora zone (zone 2), and Bruguiera zone (zone 3). Zone 1 is located in the outer portion or directly adjacent to the sea. Zone 2 is between Sonneratia zone and the adjecent land. Zone 3 is located at the rear of Rhizophora zone and only found on one track at the research site. The average salinity values on Sonneratia zone range from 33 ‰ to 35,5 ‰, whereas the range for Rhizophora is from zone 31,8 ‰ to 33,7‰ and Bruguiera zone is 33‰.Keywords: Mangrove, Bunaken National Park, Zoning, Salinity